METAL ADDITIVE MANUFACTURING WITH TOPOLOGY OPTIMIZATION METHODOLOGY FOR INNOVATIVE STRUCTURAL DESIGN - Doncheva, Elisaveta; Petreski, Martin; Zdraveski, Filip (University of Novi Sad, Faculty of Technical Sciences, Department of Industrial Engineering and Management, 2023)
Metal additive manufacturing (MAM) is an exciting manufacturing process that has recently received a lot of scientific attention due to its ability to develop stress-optimized structural elements and products in a material-efficient, cost-effective manner. Indeed, MAM also known as rapid prototyping or three-dimensional printing of metal products, is one of the most promising aspects of manufacturing highly complex geometries. It is now regarded as a source of opportunities for achieving true design-optimized manufacturing through topology optimization methodology. This methodology can improve material distribution by generating complex geometries that are easily built layer by layer using data from a three-dimensional (3D) model. The article is intended to explore the current state of process development and investigates the future potential of topology-optimized design approaches for MAM in developing lightweight and effective products. It discusses the most recent research efforts and topology optimization applications on various products and how current techniques can produce structural elements with significant weight reduction. The study demonstrates the need for additional research in industrial structure optimization and design, and it emphasizes the importance of integrating appropriate material, process, structure efficiency, and performance characterization when using topology optimization to pursue flexible and high-performance products.
Keywords: additive manufacturing, computer-aided engineering (CAE), 3D printing, topology optimization